Model for Increasing Micro and Small Enterprises Performance through Optimizing the Role of BUMDes - Ni Kadek Sinarwati; Luh Gede Kusuma Dewi; Febry Sugiantara; Bhisma Putra Wasuka; Sayu Anggi Safitri (Universitas Pendidikan Ganesha, 2021)
The micro and small enterprises (MSEs) performance inequality between districts/cities is a must-be-solved problem since inequality is one of the issues concerned in the Sustainable Development Goals. Much previous research on the role of Village-Owned Enterprises (Badan Usaha Milik Desa—BUMDes) performance revealed that BUMDes had a positive but not significant role. The reason is that BUMDes had not played an optimal role. This study aimed at building a model for improving the performance of Micro and Small Enterprises (MSEs) through optimizing the role of BUMDes. The data collected was primary data consisting of the causes of low MSEs performance, challenges, and opportunities for optimizing the role of BUMDes in improving MSE performance. Data were collected through a structured interview, in-depth interview, and Focus Group Discussion (FGD) methods. The results revealed that the model for improving MSEs' performance through optimizing the role of BUMDes was named the Dream House Model. This model requires that MSEs set a dream of experiencing a performance improvement that was set within three years. The main pillar in achieving this dream was that MSEs should revitalize and collaborate.